Analisis Efektivitas Magang pada Program Merdeka Belajar Kampus Merdeka di Seluruh Indonesia - Widiastu, Pari Mahayu; Katika, Lindawati (PAKAR Pendidikan, 2023)
Indonesia has an unemployment rate above the world average in the last five years (2017-2021). In Southeast Asia, Indonesia has the second highest unemployment rate after Brunei Darussalam. This needs to be given attention according to the Sustainable Development Goals (SDG) point 1 "No Poverty" and point 8 "Decent Work and Economic Growth". The Ministry of Education and Research and Technology as an Indonesian state institution engaged in education inaugurated an internship program at Merdeka Belajar-Kampus Merdeka (MBKM) as a solution for connecting students with industry. The study aims to analyze the effectiveness of the MBKM Internship throughout Indonesia, especially batches 1 and 2 and to analyze the differences in the effectiveness of the two batches. The method used is quantitative by analyzing the effectiveness with the context-input-process-product (CIPP) model and analyzing the differences with the Mann-Whitney different test and interpreting the results with the descriptive analysis method. The results showed that the implementation of the program was considered effective in terms of participants' perceptions. Improvements are needed in increasing the leadership agenda, increasing debriefing from field supervisors regarding future reflection, socializing and conveying good ideas, strengthening intrinsic motivation, ensuring ease of communication between stakeholders and participants, ensuring evaluation by mentors, facilitating weight equalization study and improve timeliness in disbursing pocket money. The effectiveness of batch 1 and batch 2 is not much different.